A Juridical Review of the Limitation on the Duration of Fixed-Term Employment Agreements (PKWT) Following Constitutional Court Decision Number 168/PUU-XXI/2023 in Protecting Workers’ Rights in Indonesia - David Budi; Diding Rahma; Ardison Asri (Indonesian Journal of Law and Justice, 2026)
This study aims to analyze the limitation of Fixed-Term Employment Agreements (PKWT) based on Constitutional Court Decision Number 168/PUU-XXI/2023 and to examine the legal consequences for employers and workers if PKWT exceeds the maximum five-year term. This research employs a normative legal method using statutory and conceptual approaches by analyzing labor law regulations and relevant legal doctrines concerning employment agreements. The study focuses on examining the legal interpretation and binding force of the Constitutional Court decision related to PKWT duration limits. The results demonstrate that the five-year maximum duration of PKWT constitutes an imperative legal norm designed to ensure legal certainty, balance of rights and obligations, and protection of workers’ job security. The Constitutional Court decision clarifies the ambiguity in previous regulations regarding PKWT duration, thereby preventing potential misuse of fixed-term contracts that may disadvantage workers. If employers implement PKWT exceeding the five-year limit, the employment relationship automatically converts into an Indefinite-Term Employment Agreement (PKWTT) by operation of law. This conversion imposes additional legal responsibilities on employers, including the obligation to provide stronger employment guarantees and fulfillment of normative labor rights. Therefore, the decision reinforces the legal framework governing fixed-term employment arrangements while strengthening worker protection within Indonesia’s labor law system.